Rationing of nursing care and nurse-patient outcomes: a systematic review of quantitative studies - Papastavrou, Evridiki; Andreou, Panayiota; Efstathiou, Georgios (My University, 2014)
Abstract Bedside rationing in nursing care refers to withholding or failure to carry out certain aspects of care because of limited resources such as time, staffing or skill mix. The absence of previous systematic reviews on nursing care rationing leads to a gap of synthesized knowledge on the factors and processes related to rationing and the potential negative consequences on both patients and nurses. The aim of this study was to gain an in-depth understanding of the factors and processes related to nursing care rationing. Selected papers were methodologically assessed based on their design, sampling, measurement and statistical analysis. Seventeen quantitative studies were reviewed, and findings were categorized into four themes: elements of nursing care being rationed, causes of rationing, nurse outcomes and patient outcomes. Results revealed that communication with patients and families, patient ambulation, and mouth care were common elements of rationed care. Nurse-patient workload and communication barriers were reported as potential causes of rationing. Patient-related outcomes included patient falls, nosocomial infections and low patient satisfaction levels. Nurse-related outcomes included low job and occupational satisfaction. In addition, rationing appears to be an important organizational variable linked with patient safety and quality of care. This review increases understanding of what is actually occurring at the point of care delivery so that managers will be able to improve processes that lead to high quality of care and better patient and nurse outcomes.
Keywords: Missed care; Nursing care; Rationing; Systematic review